4 steps for reliable and accurate metrics for student’s ability using Winsteps / Mohd Nor Mamat and Siti Fatahiyah Mahamood - Mamat, Mohd Nor; Mahamood, Siti Fatahiyah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Normal practice in formal examination never have accurate measure (metrics) of student's ability, as it merely counts the score of every question to be considered for student's marks. How to assess accurate metrics for student's ability performance, reliably and easily for all educators practice? Measurement of student's performance must be assessed for right and desired learning outcomes, using right and reliable instrument, with right and accurate measure scale for student's answers. Using Rasch model with Winsteps software, student’s answer will be analyzed via 4 simplified steps with preset templates to produce accurate student's ability score within psychometric scale and percentile marks, with scientific reliability level for each student's responses. Rasch model manipulates student's answer into ratio-based log odd unit.